Development of guided inquiry model mathematics learning tools to practice critical thinking skills for students in linear program materials - Nerva Nur Opticia; Siti Khabibah; M Masriyah (SAINTIS Publishing, 2022)
This study aims to describe the process of developing the device and producing a good quality guided inquiry model mathematics learning tool on linear program material for class XI SMA, and to describe the effectiveness of guided inquiry model mathematics learning which can train students' critical thinking skills on linear program material. This type of research is development research (RnD). The learning tools developed in this study are the Learning Implementation Plan (RPP), Students Worksheet (LKPD), and Critical Thinking Ability Test (TKBK) are developed using a 4-D development model which consists of four stages, namely the define stage, the design stage, the develop stage, and the disseminate stage. The research subjects for the trial class were 13 students of class XI MIPA 3 and the research subjects for the implementation class were 17 students of class XI MIPA 1. Based on the results of descriptive analysis, it was found that the learning tools developed were of good quality because they met valid, practical, and effective criteria. The learning device is said to be valid because all validators give a minimum score of 3 for each aspect of the assessment on a scale of 1-4 and the critical thinking ability test questions meet the valid, reliable, and sensitive criteria. The learning device is said to be practical because the teacher's activities in managing learning meet good criteria and the activities of students meet the active criteria. Learning devices are said to be effective because students 'responses to learning devices and learning activities meet the positive category, guided inquiry mathematics learning model to train students' critical thinking skills is achieved.